Design of an ultra wideband low noise amplifier for cognitive radio applications / Tey Yong Yuen - Tey, Yong Yuen (2017)
Since the release of 3.1 GHz – 10.6 GHz bandwidth for unlicensed radios operation in 2002 and allowing unlicensed radios to operate in the TV white space, ultra-wideband communication has become more favorable due to its high data transfer rate. However, in order to avoid unlicensed radios to interfere with underutilized licensed radios, a software has to be developed to monitor the spectrum frequency. Cognitive radios (CR) are introduced in 2000 to overcome the spectrum crowding and underutilization issues due to the increase amount of communication systems and static frequency allocation by Federal Communications Commission (FCC). CR is a hardware driven software communication system that continuously monitors the RF spectrum to determine the available band for unlicensed users, react by changing its operating frequency band and upon request from licensed user, withdraw from the frequency band without causing interference to other users. An ultra-wideband low noise amplifier (LNA) ranging from 50 MHz – 10 GHz frequency adapting resistive feedback and self-biasing techniques is designed to fulfill the requirement of CR front end transceiver. By using common source topology, the proposed LNA is able to achieve an ultra-wideband frequency response in gain and noise figure performance. Measured results show that the input and output matching are better than -10 dB with a gain of 10.32 to 13.28 dB, noise figure of 3.29 to 6 dB with a third-order intercept point ranging from -3.2 to +6 dBm in a frequency span from 50 MHz to 10 GHz using standard CMOS 0.13μm platform. The designed architecture occupies 0.77 mm2 chip area and consumes 31.2 mW of DC power from 1.2V DC supply headroom power supply.